Gambaran Penurunan Tinggi Fundus Uteri dan Pelaksanaan Senam Nifas Pada Ibu Postpartum di Kelurahan Sambikerep Kota Surabaya - Widi Astuti, Wuri; Mustofa, Linda Andri; Kumalasari, Eki (STIKES dan AKZI Karya Husada Kediri, 2024)
One indicator of success in the process of uterine involution is the achievement of a normal reduction in the height of the uterine fundus, one of the factors that support this success is by doing postpartum exercises. Failure in the process of uterine involution can result in subinvolution and will cause bleeding or postparum haemorage and even death. The purpose of this study was to find out the description of the decrease in uterine fundal height and the implementation of postpartum exercise in the Sambi Kerep Village, Surabaya City. The design in this study uses a descriptive design with a quantitative approach. The population in this study were all normal postpartum mothers on the 7th day in Sambikerep sub-district, Surabaya city with 40 respondents as research subjects, using a non-probability data collection technique and the sampling used was the total technique, the time of this study was June 14 - July 25 2023. The variables in this study are descriptions of a decrease in the height of the uterine fundus and the implementation of postpartum exercises. Data collection was carried out using questionnaires and observation sheets. Data analysis using univariate analysis was carried out to observe fundal height measurements using metlin. The results of the study showed that the decrease in uterine fundal height in mothers who did routine exercise mostly decreased in the normal category, namely 12 respondents (60%) and mothers who did not. routine postpartum exercise there are 13 respondents (65%) in the slow category. Thus one of the efforts that can be given to prevent bleeding is to do postpartum exercise.